(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The data about two new for Ukraine species of the genus Orbilia Fr. – Orbilia comma Graddon and O. flavidorosella Rehm are given. The species O. comma is reported for the first time in Eastern Europe. Both species were identified during studies of apothecial ascomycetous fungi, conducted in the territory of the Kharkiv Forest-Steppe in 2010–2017, as well as during revision of materials from scientific mycological herbarium of V.N. Karazin National University of Kharkiv CWU Myc. The work contains original descriptions, illustrations and data on the distribution of the aforementioned species in Ukraine and worldwide. Taking into account these species, and the record of O. crystallina, reported earlier, a total of 20 species of the Orbilia genus are recorded in Ukraine up to date.